UPAYA MENINGKATKAN PEMAHAMAN SELF MANAGEMENT MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING PADA SISWA KELAS X IPA SMA NEGERI 7 KOTA BENGKULU - HENI SULUSYAWATI; SYAMSUDDIN SYAMSUDDIN; YAYUK OKTA PURNAMASARI (Psikodidaktika, 2019)
This study aims: (1) to determine the level of self management in the learning of class X IPA students before getting group guidance services, (2) to determine the level of self management in learning X grade science students after receiving group guidance services, and (3) to find out group guidance services can improve self management in learning grade X IPA students before and after being given group guidance services. This research method is action research in counseling and guidance services (PTBK). The data collection techniques used in this study are questionnaires, observations, and documentation. Data analysis in this study used descriptive quantitative data analysis using the percentage formula. The results showed that: (1) The level of self management in learning class X students before being given group guidance with the role playing technique was in the low category with an average score of 68, (2) The level of self management in students of class X IPA after getting service group guidance with role playing techniques is in the high category with an average score of 109, (3) the level of self management in learning grade X IPA students experienced a good increase, before being given group guidance services using the role playing technique of self management level with a low score 68 and after being given group guidance services using role playing techniques there was an increase with an average score of 109. This shows that there was a significant increase in the low category to be high with a score of 41.